Effect of hydrate on permeability in porous media: Pore-scale micro-simulation. (November 2018) - Hou, Jian; Ji, Yunkai; Zhou, Kang; Liu, Yongge; Wei, Bei
Highlights: The effect of hydrate on permeability variation is studied by LBM. The control seepage channel determines the change characteristics of permeability. A new model of permeability is proposed on basic of the control seepage channel. Relation between permeability variation and hydrate saturation is proposed. Abstract: The permeability variation caused by hydrate dissociation will affect the further exploitation of hydrate resources during the development of natural gas hydrate. To study the effect of hydrate on seepage characteristics in hydrate-bearing sediments, the micro-flow simulation was carried out by the lattice Boltzmann method. The effect of factors related to the pore-scale distribution of mineral particle and hydrate on permeability variation was analyzed in the two-dimensional porous media. Results show that the mineral particles arrangement has no effect on permeability variation for the two-dimensional homogeneous porous media, the permeability variation is sensitive to the hydrate-formation habit and hydrate-distribution morphology in the pore center. The concept of "control seepage channel" is proposed through comparative analysis of velocity field distribution. It controls the change characteristics of permeability. Based on the control seepage channel size and the control seepage channel tortuosity, a new model is presented to measure the permeability in porous media with gas hydrate. Considering two hydrate-formation habits: grain-coating and pore-filling, the relationships between relative permeability and hydrate saturation are proposed to describe permeability variation. The relationship of pore-filling case agrees well with the experimental results. It shows that hydrate grows mainly in the pore center under the experimental conditions.